Site suitability to tourist use or management programs South Marsa Alam, Red Sea, Egypt - MOHAMMED S. A. AMMAR; MOHAMMAD HASSANEIN; HASHEM ABBAS MADKOUR; AMRO A. ABD-ELGAWAD (Nusantara Bioscience, 2011)
Ammar MSA, Hassanein M, Madkour HA, Abd-Elgawad AE. 2011. Site suitability to tourist use or management programs South Marsa Alam, Red Sea, Egypt. Nusantara Bioscience 3: 36-43. Twenty sites in the southern Egyptian Red Sea (Marsa Alam-Ras Banas sector) were surveyed principally for sensitivity significance throughout the periode 2002-2003. Sensitivity of the study area was derived from internationally known criteria, the key words of each criterion and a brief description of its use was described. The present study assigned for the first time a numerical total environmental significance score that gives a full sensitivity significance evaluation for any site to decide to select either for tourist use or management purposes. However, the results of the study still have the availability to arrange sites with respect to one criterion or only two or many of the used criteria whichever needed. Sites selected for protection are categorized as belonging to the following protected area categories: sites 7, 10 (category vi), site 18 (category ib), site 5 (category iv), sites 16, 17 (category ii). Sites selected for tourist uses are suggested to be classified into 2 categories: first category sites (sites 1, 3, 8, 11, 13, 15) which are recommended as tourist use sites with management of the sensitive resources beside non consumptive recreational activities like swimming, diving, boating, surfing, wind-surfing, jet skiing, bird watching, snorkelling, etc.; second category sites (sites 2, 4, 6, 9, 12, 14, 19, 20) which are recommended as tourist use sites with both non consumptive and managed consumptive recreational activities like fishing.